CP-072 Current venous thromboembolism prophylaxis peri-coronary artery bypass grafting at st thomas' hospital. (25th February 2017) - CHIANG, LC; Collings, V; Bates, I
Abstract : Background: Venous thromboembolism (VTE) is strongly associated with postoperative death and readmission after coronary artery bypass grafting (CABG) surgery, especially in urgent patients with a high risk of VTE. In the literature review, prophylaxis using pharmacological methods and mechanical prophylaxis were both shown to be beneficial in terms of VTE rate. CABG patients follow St Thomas' Hospital's general venous thromboprophylaxis guideline which requires pharmacological and mechanical prophylaxis. Therefore, an audit is necessary to review VTE prophylaxis peri-surgery for urgent and elective CABG patients and compare it to the literature. Purpose: To understand current practice and further assess VTE rate and side effects between elective and urgent CABG patients, and to propose adjustments to the hospital's guideline if necessary. Material and methods: Patients receiving CABG from 9 May 2016 to 17 June 2016 were selected as the audit cohort. The observational design was conducted from their admission to discharge. IBM SPSS 22.0 was used to present the results of this audit. Results: 53 patients were included in the data analysis, comprising 23 urgent patients and 30 elective patients. Mean age of the cohort was 65.3 (±9.8) years, and the men population accounted for the majority (n=47, 88.7%). In the urgent group, half of the patients received prophylaxic doses of dalteparin once daily (n=12, 52.2%), followed by 4 patients (17.4%) who received the dose for acute coronary syndrome. Antiplatelet therapy was used before CABG surgery in 18 urgent patients (78.3%). Also, all patients were given dalteparin (prophylaxic dose: n=45, 84.9%; treatment dose: n=8, 15.1%) and dual antiplatelets after CABG. There was no symptomatic VTE events within the audit period. Nevertheless, 5 urgent patients (9.4%) suffered from moderate to severe bleeding incidences during surgery, with a significant difference between groups (p=0.012). Conclusion: Under the strict VTE prophylaxis regimens, the symptomatic VTE rate seemed to be low. Despite its relatively high incidence, bleeding in urgent patients can be managed by transfusions. Therefore, no amendment was added to the guideline. Nonetheless, compliance with it could be improved. Also, mechanical prophylaxis could be considered, as evidence from the literature review suggests that it can reduce the asymptomatic VTE rate. No conflict of interest